Abuse of parental rights: general characteristics, forms, and types - O. G. Yushkevych (Bulletin of Kharkiv National University of Internal Affairs)
The article is dedicated to the author’s perspective on the scientific and legislative resolution of the issue of abuse of parental rights. Special attention is given to the exploration of scientific approaches, national legislation, and judicial practice regarding the definition and use of the term “abuse of parental rights”.